Partial HELLP Syndrome: maternal and perinatal outcome - Abbade, Joelcio Francisco; Peraçoli, José Carlos; Costa, Roberto Antonio Araújo; Calderon, Iracema de Mattos Paranhos; Borges, Vera Therezinha Medeiros; Rudge, Marilza Vieira Cunha (São Paulo Medical Journal, 2002)
CONTEXT: HELLP syndrome is a severe complication of pregnancy characterized by hemolysis, elevated liver enzymes and low platelet count. Some pregnant women develop just one or two of the characteristics of this syndrome, which is termed Partial HELLP Syndrome (PHS). OBJECTIVE: The objective of this study was to evaluate the repercussions on maternal and perinatal outcomes among women that developed PHS and to compare these women with those whose gestational hypertension or preeclampsia did not show alterations for HELLP syndrome in laboratory tests. DESIGN: Observational, retrospective and analytical study. SETTING: Maternity Department of Hospital das Clínicas, Faculdade de Medicina de Botucatu, Universidade Estadual Paulista, Botucatu, São Paulo, Brazil. SAMPLE: Pregnant or post-delivery women who had a blood pressure elevation that was first detected after mid-pregnancy, with or without proteinuria, between January 1990 and December 1995. MAIN MEASUREMENTS: Analysis was made of maternal age, race, parity, hypertension classification, gestational age at the PHS diagnosis, alterations in laboratory tests for HELLP syndrome, time elapsed to discharge from hospital, maternal complications, mode of delivery, incidence of preterm birth, intrauterine growth restriction, stillborn and neonatal death. RESULTS: Three hundred and eighteen women were selected; forty-one women (12.9%) had PHS and 277 of them (87.1%) did not develop any of the alterations of the HELLP syndrome diagnosis. Preeclampsia was a more frequent type of hypertension in the PHS group than in the hypertension group. None of the women with isolated chronic hypertension developed PHS. The rate of cesarean delivery, eclampsia, and preterm delivery was significantly greater in the PHS group than in the hypertension group. CONCLUSION: We observed that aggressive procedures had been adopted for patients with PHS. These resulted in immediate interruption of pregnancy, with elevated cesarean rates and preterm delivery. Such decisions need to be reviewed, in order to reduce the cesarean rate and the incidence of preterm delivery.